HUBUNGAN PENGGUNAAN KONTRASEPSI SUNTIK 3 BULAN DEPO MEDROKSI PROGESTERON ACETATE (DMPA) TERHADAP PENINGKATAN BERAT BADAN PADA AKSEPTOR KB - De Yesus, Aljira Kristina; Wati, Dwi Retno; Suryani, Lilis (PRIMA WIYATA HEALTH, 2024)
Hormonal contraceptives injectable three months Depo Medroxy Progestrerone Acetate (DMPA) is one of the contraceptive methods that are widely used have good effectiveness but also have side effects such as menstrual disorders form bleeding spotting amenorrhea outside menstrual cycle addition there is an increase body weight on the use of DMPA contraceptives. This type research analytic correlation with cross sectional approach population in this study all acceptors injection family planning three months in TPMB NY”S” Jabon Village Jombang Regency 40 people and the sample partly acceptor injection family planning many as 32 people sampling using sampling probability sampling technique by means simple random sampling and using checklist sheet The results showed that respondents who increased BB injection KB three months were almost all 26 respondents (80.2%), while respondents who did not increase BB using KB injection three months were 6 respondents (18.8%). The results of the analysis using Chi-Square Test with α 0.05. it was found that ρ = 0.002 < 0.05 which means that there a relationship between the use of injectable contraceptives three months Depo Medroksi Progesterone Acetate (DMPA) to increase body weight in family planning acceptors in TPMB NY “S” Jabon Village, Jombang Regency. The solution of the above problems involve midwives as health workers who must conduct counseling explain to family planning acceptors about weight gain that occurs after use is recommended adjust diet if excessive weight or can be recommended other contraceptives.